Assessment of communication skills using telehealth: considerations for educators - Wright, Hattie H.; O’Shea, Marie-Claire; Sekula, Julia; Mitchell, Lana J. (Frontiers in Medicine, 2022)
Objective. The main aim of this study was to explore the views and perceptions of dietetic educators on their ability to assess communication skills of undergraduate student dietitians in a telehealth setting. A secondary aim was to provide recommendations to educators when assessing these skills using telehealth. Methods. A descriptive qualitative study design was used. Australian and New-Zealand dietetic educators used a validated global communication rating scale to evaluate three pre-recorded telehealth encounters. Educators then answered a series of open-ended questions on their ability to assessed communication skills in the telehealth environment. Analysis. Inductive analysis allowed the emergence of themes and sub-themes independent of a specific framework or theory. Peer debriefing and triangulation increased research rigor. Results. Twenty-four educators were included in this study with the majority (87.5%) having >10years experience as a dietetic educator, and 41.6% (n=10) with experience in assessing dietetics student using telehealth. Most (76%) educators reported the assessment of non-verbal communication skills were challenging in the telehealth environment. Five themes and 15 subthemes emerged relating to advice for students and educators when assessing communication skills and a checklist was developed from recommendations that students and educators can use when preparing, planning, implementing, and assessing telehealth consultations. Conclusion. Assessing student communication skills via telehealth provides a useful opportunity with the growing use of the online environment, however it also presents challenges that must be taken into consideration. While verbal communication skills are easier to assess than non-verbal, both need to be adapted for the telehealth setting.